2014
DOI: 10.1007/s10346-014-0538-1
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of movement in the Ventnor landslide complex, Isle of Wight, southern England

Abstract: Abstract:The patterns of ground movement were monitored within a large, deep-seated landslide complex at Ventnor in southern England, between May 1998 and June 2002 using automated crackmeters, settlement cells and vibrating wire piezometers. It was found that the landslide maintains a state of marginal instability, such that it is subject to continual very slow deformation. Movement is primarily on a low-angled basal shear surface at >90 metres depth.The movement record shows a series of distinct deformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 19 publications
5
10
0
Order By: Relevance
“…10 4f.) Similar behaviour has been observed in non-brittle landslide materials Carey et al, 2015) and in remoulded materials (Ng and Petley, 2009;Carey and Petley, 2014). Thus, behaviour is conventional as a brittle first time failure and followed by ductile reactivation.…”
Section: Deformation Response To Changes In Pore Water Pressuresupporting
confidence: 70%
“…10 4f.) Similar behaviour has been observed in non-brittle landslide materials Carey et al, 2015) and in remoulded materials (Ng and Petley, 2009;Carey and Petley, 2014). Thus, behaviour is conventional as a brittle first time failure and followed by ductile reactivation.…”
Section: Deformation Response To Changes In Pore Water Pressuresupporting
confidence: 70%
“…Carey et al 2015) revealed the importance of the relationship between the level of groundwater and pore water pressure. With respect to the fact, that our area of study does not allow us to equip the landslide like in less remote areas, we are looking at the influence of precipitation on slope movement reactivation.…”
Section: Introductionmentioning
confidence: 99%
“…The same study reviewed council records between 1995 and 2005 for Bath Road and Newport Road, which indicated subsidence of 33.2 and 22 mm a −1 , respectively. Carey et al [32] identified a lag between high rainfall events and pore pressure generation, where a response was recorded after 7 days, however it took approximately 29 days to reach a peak, which then lasted approximately 30 days. The highest rainfall events did not yield the largest displacement responses, rather prolonged rainfall periods led to a higher generation of pore pressures, resulting in larger displacements.…”
Section: Historical Movement and Previous Monitoring Surveys At Ventnormentioning
confidence: 99%